Making Sure of Maths / Metric Edition: Book 3 - Quinn T.A; Watson T.F (Holmes Mcdougall Ltd, 1970)
Looking Back, Multiplication and Division, Time, Money, Decimals, Fractions, Length, Weight, Roundabout, Angles, Parallel Lines, Set-Squares, Rhombus and Kite, Area, Scales and Plans, The Circle, Shapes Make Shapes, Symmetry, Sets, Numbers from Numbers, Counting Bases, Number Patterns, Number Sentences, Graphs, Solids, Skeleton Solids, Volume, Making Sure, Work Cards, Useful Information.